Classroom Management Strategies in Fiqh Learning on the Material of Obligatory Prayers at MI An Nur Krian Sidoarjo - Kusnul Munfa'ati; Wahyuningsih A., Sinta; Zumaro, Siti (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to describe the classroom management strategies applied in Islamic Jurisprudence (Fiqh) learning, specifically the material of Fardhu Prayer for second grade students at Madrasah Ibtidaiyah (MI) An Nur Krian. The background of this study emphasizes the importance of Islamic Jurisprudence learning that is not only theoretical but also includes practical, affective, and spiritual approaches, which are specifically adapted to the developmental characteristics of children of Madrasah Ibtidaiyah age. A qualitative descriptive method was used with data collection techniques of observation, interviews, and documentation. The results of the study show five main strategies used by teachers: (1) learning planning based on direct prayer practice, (2) classroom arrangement resembling rows, (3) use of visual media such as motion cards and learning videos, (4) reinforcement of positive behavior through rewards and praise, and (5) an affective and spiritual approach in which the teacher acts as a role model. These strategies effectively create a conducive classroom atmosphere, increase student engagement, and foster internalization of sincerity in worship. This study confirms that appropriate classroom management in Islamic Jurisprudence learning has a significant influence on the success of value-based religious education in early childhood. These findings can be a reference in developing a fiqh learning model based on character formation and practical experience in Islamic elementary schools.